El ambiente social familiar y su influencia en el desarrollo integral de los niños de preparatoria trabajo previo a la obtención del título de magister en educación. - Gualsaquí, Diana M. (2022)
This research has the purpose to identify the influence of the socio familiar environment in the integral development of the kinder garden students through the analysis of theorical andscientifical information and a social familiar study. Establishing in this way its importancein the children´s development and learning at UECIB “San Juan de Ilumán”. This researchsearch for contributing the relationship between the socio familiar background and thecognitive, psychomotor and socio affective development. The methodology used is quantitative with a descriptive level that produces scaffolding of essential characteristics of the researched population. The type of research used was documental in order to review the theorical foundation and field research in order to assist to the place of facts. The methodsused were inductive, deductive and analytical-synthetic which help to gather up the results of the diagnosis with researching strategies such us observation, interviews and surveys. Thetheorical foundation which support this research is the family and its importance as the unique center of the society, the socio familiar environment as the integral development of children in their cognitive, psychomotor and socio affective area. The results of the researchshow that the children don´t have the enough affection, love and comprehension in his familiar environment in order to develop themselves in their safe bond. At the same time, the children are shy, aggressive, a few uncommunicative. In their school work is seen thatthe children are not so participative, some have a low level of attention and their work class is not made accurately.